Experimental Investigation on The Effect of PolyVinyl Alcohol on Cement Fluid Loss in Oil Wells - Awl, Mohammed Jamal; Abdulla, Atta Sheakh Karim; Tayeb, Nabil Adil (Kurdistan Journal of Applied Research, 2020)
This study presents the effect of PolyVinyl Alcohol Cement Fluid Loss Additive (PVA FLAC) on the API Filtration property of a cement slurry. In Cementing operations of oil wells, different type of fluid loss agents and chemicals are used based on the condition of the wells. PVA FLAC recently introduced in Kurdistan oil industry as loss agent additive to reduce the API Filtration Rate and fluid loss of the cement slurry. Four cementing formulations with different concentration of PVA FLAC additive prepared and their API filtration rates are measured. The results showed that when adding 1.94 gm, 2.91 gm and 3.88 gm of PVA FLAC additive to the cement slurry, the API Filtration Rate reduced by %17, %29 and %42, respectively. The new concentration significantly reduced the rate of filtration when compared to using only 0.97 gm of PVA FLAC additive.